The effect of physical and biological pre-treatments of oil palm fronds on in vitro ruminal degradability - Rusli, Nor Dini; Azmi, Mohammad Azri; Mat, Khairiyah; Che Harun, Hasnita; Mohamed, Wan Zahari; Kasim, Azhar; Saad, Mohd Zamri; Abu Hassim, Hasliza (Universiti Putra Malaysia Press, 2019)
Physical pre-treatment of the oil palm frond (OPF) is known to loosen the lignocellulose while the biological pre-treatment is capable in degrading the lignin, making the substrates more accessible for rumen microbes. This study aimed at assessing the efficacy of physical, biological and combination of both pre-treatments of OPF on the in vitro ruminal degradability. Five different samples of OPF pre-treatments were used in this study; OPF was subjected to the physical pre-treatment (POPF), OPF to the biological pre-treatments using an enzyme extract of each Ganoderma lucidum (BGL) and Lentinula edodes (BLE), respectively. Another two samples were subjected to a combination of physical and biological pre-treatments of G. lucidum (CGL) and L. edodes (CLE) respectively. The control was non-treated OPF. Two fistulated Katjang goats consuming 440 g/kg OPF and 897 g/ kg commercial pellet daily on dry matter basis were used as rumen fluid donors. In vitro incubation was carried out at 39°C for 24 hours. Proportions of volatile fatty acid were measured at the end of incubation by gas chromatography. Results showed that concentrations of lignin following all pre-treatment methods were significantly lower (p<0.05) at 150(POPF), 90(BGL), 119(BLE), 100(CGL) and 120(CLE) g/ kg DM as compared to the FOPF (190 g/kg). After 24 hours of incubation, the cumulative gas of all treatment groups differed significantly from FOPF. Both BGL and CGL showed significantly higher propionate and butyrate concentrations as well as apparent rumen degradable carbohydrate with 6.57 mg and 6.54 mg, respectively as compared to the FOPF. It appeared that BGL and CGL resulted in higher lignin degradation that increased the in vitro rumen degradability. In conclusion, biological pre-treatment with enzyme extract of WRF, either alone or in combination are promising to improve the quality of OPF.